C++ from the beginning. - Skansholm, Jan, ....- (Harlow : Addison-Wesley, 2002)
1.Computers and programming 2.The basics 3.Characters and texts 4.Functions 5.Types 6.Object-oriented program development 7.Classes 8.More about classes 9.Inheritance 10.Exceptions 11.Streams and files 12.Container classes and algorithms 13.Dynamic data structures 14.Templates 15.The final pieces of the puzzle
Keywords: C++ (programmeertaal).